2013
DOI: 10.1159/000355706
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Relevance of Allergic Rhinitis in Patients with Classic Asthma and Cough Variant Asthma

Abstract: Background: A clinically relevant relationship between classic asthma and allergic rhinitis has been reported. However, the possible link between cough variant asthma (CVA) and allergic rhinitis remains unknown. Objectives: To clarify the prevalence and clinical relevance of perennial allergic rhinitis or seasonal allergic rhinitis in CVA patients compared to classic asthma patients. Methods: We retrospectively studied adult patients with classic asthma (n = 190) and those with CVA (n = 83). The prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 51 publications
(61 reference statements)
4
34
1
Order By: Relevance
“…Allergic rhinitis is a predictor of greater severity of asthma when asthmatics were not stratified by age at onset [26,27]. However, 2 longitudinal studies showed that childhood allergic rhinitis is associated with asthma persistence [28] and atopic asthma, but not nonatopic asthma in adulthood [29].…”
Section: Discussionmentioning
confidence: 99%
“…Allergic rhinitis is a predictor of greater severity of asthma when asthmatics were not stratified by age at onset [26,27]. However, 2 longitudinal studies showed that childhood allergic rhinitis is associated with asthma persistence [28] and atopic asthma, but not nonatopic asthma in adulthood [29].…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Furthermore, a previous study found that perennial allergic rhinitis was associated with high FeNO levels and more severe asthma. 21 These observations indicate that high FeNO levels are related more severe eosinophil infiltration in the airway. However, in normal adults, agerelated variations in FeNO data are inconsistent.…”
Section: Discussionmentioning
confidence: 87%
“…FeNO levels also correlated with a higher percentage of eosinophils in the sputum of patients with CVA. 21 These observations indicate that high FeNO levels are related more severe eosinophil infiltration in the airway. In our study, using FEF25-75 as the indicator, the subjects with CVA and high FeNO levels exhibited relatively lower small airway function compared with subjects with normal FeNO levels.…”
Section: Discussionmentioning
confidence: 87%
“…These symptoms of AR was downgraded by many patients as only third of them considered active management of AR as approximation of 70% of responded they do not use any medication regarding the treatment of allergic rhinitis. The literature suggested a strong link between allergic rhinitis and asthma [10]. Based on number of studies, allergic rhinitis is considered as a risk factor for asthma [10].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggested a strong link between allergic rhinitis and asthma [10]. Based on number of studies, allergic rhinitis is considered as a risk factor for asthma [10]. Both lack of awareness, education and the low severity of symptoms play a significant role in lack of seeking for treatment of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%